Mobile apps in tourism communication: the strengths and weaknesses on tourism trips - Abdul Rashid, Roswati; Ismail, Radhiah; Ahmad, Mazlina; Chua Abdullah, Nurul Ain; Zakaria, Rosdi; Mamat, Roslina (IOP Publishing, 2020)
The IR4.0 wave has fostered the variety of development of mobile apps inclusive of apps that are useful to ensure the smoothness of tourism activities. These mobile apps have replaced many of the functions of tourism workers in the tourism industry. However, the question is to what extent both the effectiveness and weaknesses of these apps can help and satisfy a tourist during his tour visit. Therefore, this concept paper will discuss the strengths and weaknesses of using mobile apps to serve the purpose of smoothening the tour visit and tourism communications. The writing of this paper is based on research focusing on the use of mobile apps in tourism from 2011 to date. the findings of the study indicate that the application of mobile apps in tourism communication isn't replacing the function of human workers in the tourism sector entirely. Although there are some strengths in using the mobile apps, on the other, it still has much weakness which requires improvements to be made to meet tourist's needs. Thus, this study will further illustrate the level of effectiveness of using mobile apps in the tourism industry as a source of reference to the mobile apps developer who created the sophisticated apps and fulfills the demand of tourists. This also will further become a reference to LR in improvising the quality of the service of a tourist destination.